Facilitating Eudaimonic Well-Being in Mental Health Care Organizations: The Role of Servant Leadership and Workplace Civility Climate - der Kinderen, Susan (Int J Environ Res Public Health, 2020)
Demanding and complex work within mental health care organizations places employee well-being at risk and raises the question of how we can positively influence the psychological well-being and functioning of these employees. This study explores the role of servant leadership and workplace civility climate in shaping eudaimonic well-being among 312 employees in a Dutch mental health care organization. The findings showed that servant leadership had a stronger relationship with eudaimonic well-being when workplace civility climate was high. Furthermore, the results showed that servant leadership was positively related to workplace outcomes, partially through eudaimonic well-being, and that this mediating process varied across different levels of workplace civility climate. This study contributes to the scholarly understanding of the role of servant leadership and a positive work climate in shaping psychological well-being at work.